Quality of life valuations of HPV-associated cancer health states by the general population. Issue 7 (29th May 2012) - Conway, E Lynne; Farmer, K Chip; Lynch, William J; Rees, Guy L; Wain, Gerard; Adams, Jane
Abstract : Objectives: To obtain health-related quality of life valuations (ie, utilities) for human papillomavirus (HPV)-related cancer health states of vulval, vaginal, penile, anal and oropharyngeal cancers for use in modelling cost-effectiveness of prophylactic HPV vaccination. Methods: Written case descriptions of each HPV-associated cancer describing the 'average' patient surviving after the initial cancer diagnosis and treatment were developed in consultation with oncology clinicians. A general overview, standard gamble questionnaire for each health state and a quiz was conducted in 120 participants recruited from the general population. Results: In the included population sample (n=99), the average age was 43 years (range = 18–70 years) with 54% men, 44% never married/43% married, 76% education beyond year 12 and 39% employed full-time. The utility values for the five health states were 0.57 (95% CI 0.52 to 0.62) for anal cancer, 0.58 (0.53 to 0.63) for oropharyngeal cancer, 0.59 (0.54 to 0.64) for vaginal cancer, 0.65 (0.60 to 0.70) for vulval cancer and 0.79 (0.74 to 0.84) for penile cancer. Participants demonstrated a very good understanding of the symptoms, diagnosis and treatment of these cancers with a mean score of 9 (SD=1.1) on a 10-item quiz. Conclusions: This study provides utility estimates for the specific HPV-related cancers of vulval, vaginal, penile, anal and oropharyngeal cancers valued by a general population sample using standard gamble. The results demonstrate considerable quality of life impact associated with surviving these cancers that will be important to incorporate into modelling cost-effectiveness of prophylactic HPV vaccination in different populations.